Alkalinized lidocaine solution as a first‐line local anesthesia protocol for intradetrusor injection of onabotulinum toxin A: Results from a double‐blinded randomized controlled trial - Pereira e Silva, Ricardo; Ponte, Carolina; Lopes, Filipe; Palma dos Reis, José (Neurourology and urodynamics, 2020)
Aims Local anesthesia protocols for intradetrusor onabotulinum toxin A (BoNTA) injection lack standardization. We aimed to determine if an alkalinized lidocaine solution is more effective than lidocaine only. Methods Patients of both genders aged 18 or above enlisted for intradetrusor BoNTA injection (idiopathic, neurogenic, and bladder pain syndrome) were included in a double‐blinded randomized controlled trial after obtaining their informed consent. All participants filled a bladder diary and a urine culture was performed. Subjects were randomized 1:1 to Protocol A (20 ml 2% lidocaine + 10 ml 8.4% sodium bicarbonate) or Protocol B (20 ml 2% lidocaine + 10 ml 0.9% saline solution). A Numeric Rating Scale (0–10) was used to assess the level of pain immediately after the procedure (primary endpoint). Secondary endpoints included pain after 1 h, urinary tract infection, acute urinary retention, and hematuria related to the procedure. Results A total of 116 patients were randomized. Baseline characteristics (age, sex, indication, and bladder diary parameters) of patients in Group A and B were similar. Pain scores at the end of the procedure were significantly lower with the alkalinized solution (Protocol A and B, respectively, 2.37 ± 0.31 vs. 4.44 ± 0.36, p < .01). No differences were observed 1 h after treatment (Protocol A and B, respectively, 0.54 ± 0.17 vs. 0.69 ± 0.19, p = .487). The only adverse event reported was mild‐to‐moderate self‐limited hematuria in 15.4% of patients. Conclusions The use of an alkalinized lidocaine solution has proven to be significantly superior to lidocaine only as local anesthesia before intradetrusor BoNTA injection, suggesting that this may be considered a first‐line option.